Enhancing Creative Thinking in Preschoolers: Teacher Strategies for Creating a Multiliteracy-Based Learning Environment - Farantika, Dessy; Afrezah, Novela Nur; Salhah; Saudah; Asiah; Yafie, Evania (Program Studi Magister Pendidikan Anak Usia Dini, 2024)
The preschool period is an important phase of child development, which includes cognitive aspects, especially in terms of growth and creative thinking, but many teachers still use conventional learning strategies. This study aimed to investigate effective teacher strategies for improving creative thinking in preschool children in a multiliteracy-based learning environment. The research method used a qualitative approach with a multisite case study research involving a kindergarten school. The informants were selected using a purposive sampling technique involving nine informants, including teachers, assistant teachers, and school principals. The research findings show that implementing the strategy steps can create a dynamic and creative learning environment that supports literacy development in various contexts. Factors such as competent teachers, access to resources, and management of barriers shape an effective multi-literacy environment. The positive impact motivates students to continue thinking creatively and exploratively. The multiliteracies approach enhances preschoolers' creativity through purposeful strategies, teacher collaboration, resource support, and the use of diverse media, which empowers literacy in education. Keywords: creative thinking, multiliteracy, teacher, preschoolers References: Auris Villegas, D., Colquepisco Paucar, N. T., Cuba Garcia, S., & Vilca Arana, M. (2021). Revista Innova Educación. Revista Innova Educación, 3(1), 6–19. Behnamnia, N., Kamsin, A., Ismail, M. A. B., & Hayati, A. (2020). The effective components of creativity in digital game-based learning among young children: A case study. Children and Youth Services Review. https://doi.org/10.1016/j.childyouth.2020.105227 Bergen, E. van, Zuijen, T. van, Bishop, D., & Jong, P. F. de. (2017). Why Are Home Literacy Environment and Children’s Reading Skills Associated? What Parental Skills Reveal. Reading Research Quarterly, 52(2), 147–160. https://doi.org/10.1002/RRQ.160 Bohn, M. F., & de Freitas, E. C. (2020). Under multiliteracy lenses: Reading and comprehension of meaning in texts of multimodal genres. Revista Conhecimento Online. https://doi.org/10.25112/RCO.V3I0.1878 Brezovszky, B., McMullen, J., Veermans, K., Hannula-Sormunen, M. M., Rodríguez-Aflecht, G., Pongsakdi, N., Laakkonen, E., & Lehtinen, E. (2019). Effects of a mathematics game-based learning environment on primary school students’ adaptive number knowledge. Computers and Education. https://doi.org/10.1016/j.compedu.2018.09.011 Cortés Loyola, C., Adlerstein Grimberg, C., & Bravo Colomer, Ú. (2020). Early childhood teachers making multiliterate learning environments: The emergence of a spatial design thinking process. Thinking Skills and Creativity, 36(March), 100655. https://doi.org/10.1016/j.tsc.2020.100655 Daulay, U., Adisaputera, A., & Eviyanti, E. (2022). Multiliteracy-Based Teaching Materials To Improve Student Understanding. https://doi.org/10.4108/eai.20-9-2022.2324513 Díaz-Díaz, M., Sanz, Y. E., & Ezpeleta, A. L. M. (2022). Reading on digital media and the reading process of teachers in training. Pixel-Bit, Revista de Medios y Educacion. https://doi.org/10.12795/PIXELBIT.91903 Do, H., Do, B. N., & Nguyen, M. H. (2023). Heliyon 3How do constructivism learning environments generate better motivation and learning strategies ? The Design Science Approach. Heliyon, 9(12), e22862. https://doi.org/10.1016/j.heliyon.2023.e22862 Evans, C. (2020). Measuring Student Success Skills: a Review of the Literature on Critical Thinking. Center For Assessment. Galaktionova, T., & Kazakova, O. (2022). Multiliterate Person: the View of Students and Teachers. Media Education (Mediaobrazovanie). https://doi.org/10.13187/me.2022.2.221 Gube, M., & Lajoie, S. (2020). Adaptive expertise and creative thinking : A synthetic review and implications for practice. Thinking Skills and Creativity, 35(August 2019), 100630. https://doi.org/10.1016/j.tsc.2020.100630 Hapidin, Pujianti, Y., Syarah, E. S., & Gunarti, W. (2023). Teacher’s Understanding of Project Learning Models through Children’s Comics with STEAM Content in Indonesia. JPUD - Jurnal Pendidikan Usia Dini. https://doi.org/10.21009/jpud.171.06 Huang, J., Zang, Y., Ren, L. H., Li, F. J., & Lu, H. (2019). A review and comparison of common maternal positions during the second-stage of labor. International Journal of Nursing Sciences, 6(4), 460–467. https://doi.org/10.1016/j.ijnss.2019.06.007 Kulju, P., Kupiainen, R., Wiseman, A. M., Jyrkiäinen, A., Koskinen-Sinisalo, K.-L., & Mäkinen, M. (2018). A Review of Multiliteracies Pedagogy in Primary Classrooms. Language and Literacy, 20(2), 80–101. https://doi.org/10.20360/langandlit29333 Kustiawan, U., & Yafie, E. (2021). The Effect of Storytelling Assisted by Pop-Up Media to Improve Language Development Skills and Attitude of Opinion. International Journal of Research and Review, 11(18), 114–128. https://doi.org/10.52403/ijrr.20210897 Malmia, W., Makatita, S. H., Lisaholit, S., Azwan, A., Magfirah, I., Tinggapi, H., & Umanailo, M. C. B. (2019). Problem-based learning as an effort to improve student learning outcomes. International Journal of Scientific and Technology Research. Miles, M. B., & Huberman, A. M. (2018). Qualitative Data Analysis: A Methods Sourcebook. Miller, T., Daugherty, L., Martorell, P., & Gerber, R. (2022). Assessing the Effect of Corequisite English Instruction Using a Randomized Controlled Trial. Journal of Research on Educational Effectiveness. https://doi.org/10.1080/19345747.2021.1932000 Murray, C. J. L., Callender, C. S. K. H., Kulikoff, X. R., Srinivasan, V., Abate, D., Abate, K. H., Abay, S. M., Abbasi, N., Abbastabar, H., Abdela, J., Abdelalim, A., Abdel-Rahman, O., Abdi, A., Abdoli, N., Abdollahpour, I., Abdulkader, R. S., Abebe, H. T., Abebe, M., Abebe, Z., … Lim, S. S. (2018). Population and fertility by age and sex for 195 countries and territories, 1950–2017: a systematic analysis for the Global Burden of Disease Study 2017. The Lancet. https://doi.org/10.1016/S0140-6736(18)32278-5 Nikkola, T., Reunamo, J., & Ruokonen, I. (2022). Children’s creative thinking abilities and social orientations in Finnish early childhood education and care. Early Child Development and Care, 192(6), 872–886. https://doi.org/10.1080/03004430.2020.1813122 Nopilda, L., & Kristiawan, M. (2018). Gerakan Literasi Sekolah Berbasis Pembelajaran Multiliterasi Sebuah Paradigma Pendidikan Abad Ke- 21. JMKSP (Jurnal Manajemen, Kepemimpinan, Dan Supervisi Pendidikan). https://doi.org/https://doi.org/10.31851/jmksp.v3i2.1862 Nuryani, P., Abidin, Y., & Herlambang, Y. T. (2019). Model Pedagogik Multiliterasi Dalam Mengembangkan Keterampilan Berpikir Abad Ke-21. EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 11(2), 117–126. https://doi.org/10.17509/eh.v11i2.18821 O’Reilly, C., Devitt, A., & Hayes, N. (2022). Critical thinking in the preschool classroom - A systematic literature review. Thinking Skills and Creativity, 46(August). https://doi.org/10.1016/j.tsc.2022.101110 Palsa, L., & Mertala, P. (2019). Multiliteracies in local curricula: conceptual contextualizations of transversal competence in the finnish curricular framework. Nordic Journal of Studies in Educational Policy. https://doi.org/10.1080/20020317.2019.1635845 Papadopoulos, I., & Bisiri, E. (2020). Fostering Critical Thinking Skills in Preschool Education: Designing, Implementing and Assessing a Multiliteracies-Oriented Program Based on Intercultural Tales. Multilingual Academic Journal of Education and Social Sciences, 8(1). https://doi.org/10.46886/majess/v8-i1/7263 Pristiwo, S. B., & Muflihah, M. (2023). Practice of the Socratic Seminar Method in Teaching Speaking at the 10th Grade of State Vocational High School 3 Purwokerto. English Education: Jurnal Tadris Bahasa Inggris. https://doi.org/10.24042/ee-jtbi.v16i1.15795 Pye, R. E., & Chan, H. H. (2023). Dynamic tests as a language-free method for assessing reading in a multilingual setting. Journal of Cultural Cognitive Science. https://doi.org/10.1007/s41809-023-00120-8 Qadri, L., Ikhsan, M., & Yusrizal, Y. (2019). Mathematical Creative Thinking Ability for Students Through REACT Strategies. International Journal for Educational and Vocational Studies, 1(1), 58. https://doi.org/10.29103/ijevs.v1i1.1483 Rahman, M. A., Melliyani, M., Handrianto, C., Erma, E., & Rasool, S. (2022). PROSPECT AND PROMISE IN INTEGRATING MULTILITERACY PEDAGOGY IN THE ENGLISH LANGUAGE CLASSROOM IN INDONESIA. ETERNAL (English, Teaching, Learning, and Research Journal). https://doi.org/10.24252/eternal.v81.2022.a3 Richard, V., Lebeau, J. C., Becker, F., Inglis, E. R., & Tenenbaum, G. (2018). Do more creative people adapt better? An investigation into the association between creativity and adaptation. Psychology of Sport and Exercise, 38(September), 80–89. https://doi.org/10.1016/j.psychsport.2018.06.001 Rosen, Y., Stoeffler, K., & Simmering, V. (2020). Imagine: Design for creative thinking, learning, and assessment in schools. Journal of Intelligence, 8(2). https://doi.org/10.3390/jintelligence8020016 Saregar, A., Cahyanti, U. N., Misbah, Susilowati, N. E., Anugrah, A., & Muhammad, N. (2021). Core learning model: Its effectiveness towards students’ creative thinking. International Journal of Evaluation and Research in Education, 10(1), 35–41. https://doi.org/10.11591/ijere.v10i1.20813 Scott-Barrett, J., Johnston, S. K., Denton-Calabrese, T., McGrane, J. A., & Hopfenbeck, T. N. (2023). Nurturing curiosity and creativity in primary school classrooms. Teaching and Teacher Education, 135(June 2022), 104356. https://doi.org/10.1016/j.tate.2023.104356 Selayani, N. K., & Bayu, G. W. (2023). Pembelajaran Berbasis Multiliterasi di Sekolah Dasar: Bagaimana Mengoptimalkannya? Jurnal Ilmiah Pendidikan Profesi Guru, 5(3), 466–478. https://doi.org/10.23887/jippg.v5i3.57400 Shah, B., & Gustafsson, E. (2021). Exploring the Effects of Age, Gender, and School Setting on Children’s Creative Thinking Skills. Journal of Creative Behavior, 55(2), 546–553. https://doi.org/10.1002/jocb.480 Sitepu, K. B., Adisaputera, A., & Lubis, M. (2022). Development of Interactive Learning Media Based on Multiliteration for Ability to Develop Exposition Texts in Class X Students of SMA Negeri 1 Salapian. https://doi.org/10.4108/eai.20-9-2022.2324547 Tang, T., Vezzani, V., & Eriksson, V. (2020). Developing critical thinking, collective creativity skills and problem solving through playful design jams. Thinking Skills and Creativity. https://doi.org/10.1016/j.tsc.2020.100696 Torrance, E. P. (1968). A longitudinal examination of the fourth grade slump in creativity. The Gifted Child Quarterly, 12(4). https://doi.org/https://doi.org/10.1177/ 001698626801200401 Trisnayanti, Y., Khoiri, A., Miterianifa, & Ayu, H. D. (2019). Development of Torrance test creativity thinking (TTCT) instrument in science learning. AIP Conference Proceedings, 2194(December). https://doi.org/10.1063/1.5139861 Ulger, K. (2018). The effect of problem-based learning on the creative thinking and critical thinking disposition of students in visual arts education. Interdisciplinary Journal of Problem-Based Learning, 12(1). Untari, E. (2017). Pentingnya Pembelajaran Multiliterasi untuk Mahasiswa Pendidikan Guru Sekolah Dasar dalam Mempersiapkan Diri Menghadapi Kurikulum 2013. Wahana Sekolah Dasar, 25(1), 16–22. https://doi.org/10.17977/um035v25i12017p016 Wu, Y., Lian, K., Hong, P., Liu, S., Lin, R. M., & Lian, R. (2019). Teachers’ Emotional Intelligence and Self-efficacy: Mediating Role Of Teaching Performance. Social Behavior and Personality, 47(3). https://doi.org/10.2224/SBP.7869 Yafie, E., Ashari, Z. M., Samah, N. A., Widiyawati, R., Setyaningsih, D., & Haqqi, Y. A. (2023). The Effectiveness of Seamless Mobile Assisted Real Training for Parents (SMART-P) Usage to Improve Parenting Knowledge and Children’s Cognitive Development. International Journal of Interactive Mobile Technologies. https://doi.org/10.3991/ijim.v17i10.37883 Yafie, E., Giavarini, I., & Maulidia, L. N. (2020). Stimulating strategy children experiencing late language emergence (LLE) during pandemic covid-19. 193–197. https://doi.org/10.2991/ASSEHR.K.201112.034 Yafie, E., Olufunke, O.-F. T., Ali, M., Robbaniyah, I., Maulidia, L. N., & Setyaningsih, D. (2021). The Combination of Imaginative Teaching Methods and Multimedia Learning in Early Childhood Education during COVID Pandemic: Social-Emotional and Language Development. Al-Athfal: Jurnal Pendidikan Anak, 7(1), 1–14. https://doi.org/10.14421/al-athfal.2021.71-01 Yildiz, C., & Yildiz, T. G. (2021). Exploring the relationship between creative thinking and scientific process skills of preschool children. Thinking Skills and Creativity. https://doi.org/10.1016/j.tsc.2021.100795